Edge nitrogen vacancy carbon nitride with room-temperature ferromagnetism as well as preparation method and application of edge nitrogen vacancy carbon nitride

By introducing nitrogen vacancy into two-dimensional carbon nitride materials with urea as raw material, the problems of complex and high cost of preparation of existing two-dimensional ferromagnetic materials are solved, and high-performance room temperature ferromagnetics are achieved, suitable for spintronic devices, Topological quantum devices and magnetic storage fields.

CN119430095APending Publication Date: 2025-02-14XIDIAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411576707.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The application of existing two-dimensional ferromagnetic materials is limited by problems such as scarcity of raw materials, low Curie temperature, complex preparation processes and biotoxicity, resulting in high cost, high energy consumption and difficulty in achieving high-performance room temperature ferromagnetics.

Method used

By calcining, grinding and annealing in argon gas in sequence, nitrogen vacancy is introduced at the edge of the carbon-nitrogen skeleton of the graphite-like phase structure of carbon nitride, and edge nitrogen vacancy carbon nitride with room temperature ferromagneticity is prepared.

Benefits of technology

The edge nitrogen vacant carbon nitride with high purity, high Curie temperature and room temperature ferromagnetic properties is achieved, reducing the preparation cost, simplifying the process flow, and avoiding the environmental and biosafety risks brought about by the use of doped elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430095A_ABST
    Figure CN119430095A_ABST
Patent Text Reader

Abstract

The invention discloses edge nitrogen vacancy carbon nitride with room-temperature ferromagnetism and a preparation method and application thereof. The edge nitrogen vacancy carbon nitride is an amorphous nanosheet and is of a graphite-like structure with an edge nitrogen vacancy. The thickness of the edge nitrogen vacancy carbon nitride nanosheet is 3-8 nm, and the length or width of the edge nitrogen vacancy carbon nitride nanosheet is 1-15 microns; the method comprises the following steps: calcining urea, grinding and annealing in an argon environment, cleaning and drying to obtain orange-red edge nitrogen vacancy carbon nitride; the preparation method disclosed by the invention has the characteristics of simple process, high efficiency and easiness in repetition, and the prepared edge nitrogen vacancy carbon nitride has the characteristics of high purity, high Curie temperature and room-temperature ferromagnetism, and can be applied to the fields of spinning electronic devices, topological quantum devices, magnetic storage and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum functional materials, and in particular relates to an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, and a preparation method and application thereof. Background Art

[0002] In 2017, the existence of two-dimensional ferromagnetic materials was first demonstrated, and significant progress has been made in many fields, especially in the fields of spin electronics and quantum materials. Therefore, transition metal and rare earth two-dimensional ferromagnetic materials with rich magnetic ordered structures have attracted widespread attention. However, the application of these materials is limited by the following problems:

[0003] 1. Scarcity of raw materials: The resources of many transition metals are limited, resulting in high cost of materials.

[0004] 2. Low Curie temperature: Low Curie temperature limits its application in high temperature environments.

[0005] 3. Complex preparation process: The synthesis process usually requires multiple steps, which increases the difficulty of research.

[0006] 4. Biological toxicity: Certain metal elements may cause potential harm to the environment and organisms.

[0007] Due to the above factors, the research and application of two-dimensional ferromagnetic materials face high costs and energy consumption. However, carbon has a band gap that is considered adjustable due to its complex bonding environment. Although the spin-orbit interaction of sp electrons is weak, it has a longer spin lifetime, which enables it to achieve room-temperature ferromagnetism at a low-dimensional scale. At present, materials such as graphene and doped graphene have achieved room-temperature ferromagnetism, but their performance is far from the usable level. Among them, carbon nitride is considered to be one of the most promising materials with carbon-based intrinsic ferromagnetism. For example, in 2022, a Chinese patent application with announcement number CN115382505A disclosed a thiol-functionalized magnetic oxidized carbon nitride, which can obtain better magnetic properties after being doped with iron, but its ferromagnetism comes from the doped iron, not intrinsic carbon-based ferromagnetism. In 2023, Lina Du et al. (Lina Du, Bo Gao, Song Xu, Qun Xu. Strong ferromagnetism of g-C3N4 achieved by atomic manipulation. Nature Communications 2023, 14, 2278) introduced a boron bridge into graphite-like carbon nitride, used 16MPa pressure of carbon dioxide gas and acidic solvent etching to achieve hydrogen bond cleavage, and increased the saturation magnetization of metal-free carbon nitride at room temperature to 0.043emu / g. The preparation method is expensive, complicated and dangerous; in 2024, Yong Wang et al. (Yong Wang, Dingyi Yang, Wei Xu, Yongjie Xu, Yu Zhang, Zixuan Cheng, Yizhang Wu, Xuetao Gan, Wei Zhong, Yan Liu, Genquan Han, YueHao. Room-temperature ferromagnetism and piezoelectricity in metal-free 2D semiconductor crystalline carbon nitride. Nano Research 2024,17,5670-5679) prepared pure crystalline carbon nitride by chemical vapor deposition, with a saturation magnetization of 0.01emu / g at room temperature, realizing the room temperature ferromagnetism of intrinsic carbon nitride; although the room temperature ferromagnetism of carbon nitride was achieved in the above existing studies, the doping process environment had poor compatibility, high cost, and the source of magnetism was the doping element, while the room temperature saturation magnetization of intrinsic carbon nitride was too low to be further applied. Therefore, the preparation of two-dimensional carbon-based materials with high magnetism and room temperature ferromagnetism is a key challenge to promote the development of spin electronics, magnetic storage, and topological quantum fields. Summary of the invention

[0008] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism and a preparation method and application thereof. Urea is used as a raw material, and calcination, grinding in argon and annealing are performed in sequence to introduce nitrogen vacancies at the edges of the carbon-nitrogen skeleton of the graphite-like phase structure of the carbon nitride. After cleaning and drying, the edge nitrogen vacancy carbon nitride with room temperature ferromagnetism is obtained. The preparation method of the present invention has the characteristics of simple process, high efficiency and easy repeatability. The prepared edge nitrogen vacancy carbon nitride has the characteristics of high purity, high Curie temperature and room temperature ferromagnetism, and can be applied to the fields of spin electronic devices, topological quantum devices and magnetic storage.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, using urea as a raw material, sequentially calcining, grinding in argon and annealing to introduce nitrogen vacancies at the edges of the carbon-nitrogen skeleton of the graphite-like phase structure of the carbon nitride, and synthesizing the edge nitrogen vacancy carbon nitride, specifically comprising the following steps:

[0011] Step 1: calcine urea by heating it to 550-650°C at 2.5-5°C / min and then keeping it at that temperature for 2-4h, and then naturally cool it to room temperature to obtain g-C3N4 powder;

[0012] Step 2: Grind and sieve the g-C3N4 powder obtained in step 1 in an argon-filled environment to obtain a powder with a sieve mesh number of 200-350 mesh;

[0013] Step 3: The g-C3N4 powder obtained in step 2 is heated to 680-800°C at 25-35°C / min in an argon environment and then kept at this temperature for 1-10 minutes for annealing to obtain an orange-red powder;

[0014] Step 4: Use a cleaning solvent to clean and dry the orange-red powder obtained in step 3 to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0015] The purity of urea in step 1 is greater than or equal to 99%.

[0016] The grinding time in step 2 is not less than 30 min.

[0017] The g-C3N4 powder used for annealing is not more than 10 mg / mm 2 .

[0018] The cleaning solvents in step 4 are diluted ammonia water, ethanol and deionized water with a molar concentration of 0.1-0.2 mol / L, and finally the cleaning is performed with deionized water. The cleaning times for each cleaning solvent are at least three times.

[0019] The cleaning operation in step 4 is ultrasonic oscillation and centrifugal removal, the ultrasonic oscillation time is ≤10min, the centrifugal speed is 4000-6000rpm, and the centrifugal time is ≥6min; the drying temperature is 60-80°C, and the drying time is at least 4h.

[0020] The present invention also provides edge nitrogen vacancy carbon nitride with room temperature ferromagnetism obtained by the above preparation method.

[0021] The edge nitrogen vacancy carbon nitride is in the form of orange-red powder and has an amorphous nanosheet structure; the amorphous nanosheet has a thickness of 3-8 nm and a length or width of 1-15 μm.

[0022] The edge nitrogen vacancy carbon nitride has nitrogen vacancies at the edges of the carbon-nitrogen skeleton while retaining a graphite-like phase structure.

[0023] The present invention also provides an application of edge nitrogen vacancy carbon nitride with room temperature ferromagnetism in spin electronic devices, topological quantum devices or magnetic storage.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention introduces nitrogen vacancies at the edges of carbon chains in a graphite-like phase structure by annealing g-C3N4 obtained by calcining urea in the atmosphere in an argon environment to obtain edge nitrogen vacancy carbon nitride with room temperature ferromagnetism; the preparation method does not require the introduction of additional doping elements, is low in cost and environmentally friendly, and the process is simple, efficient and easy to repeat.

[0026] 2. The edge nitrogen vacancy carbon nitride prepared by the preparation method of the present invention removes the amino group at the side chain of the carbon nitride nitrogen skeleton while retaining the graphite-like phase structure, making the π-electron system unsaturated, forming free electrons and unsaturated covalent bonds; the nitrogen vacancy acts as a local defect state, inducing unpaired electrons in the structure to form a local magnetic moment. The electron rearrangement caused by the unsaturation of the π-electron system leads to a strong exchange interaction between spins, thereby promoting room temperature intrinsic ferromagnetism; the edge nitrogen vacancy carbon nitride prepared by the preparation method of the present invention has room temperature ferromagnetism, and its Curie temperature exceeds 400K, the saturation magnetization is not less than 0.065emu / g at a temperature of 2K, and the saturation magnetization is not less than 0.045emu / g at a temperature of 300K.

[0027] In summary, the edge nitrogen vacancy carbon nitride prepared by the present invention has the characteristics of high purity, high Curie temperature, room temperature ferromagnetism, no metal components, light weight, low cost and environmental protection. It can be used in a wide range of magnetic demand scenarios, especially in biomagnetism, medical diagnosis, food and drug processing, environmental protection, etc. It has great potential; it also provides a new material platform for the future research of spintronic devices, topological quantum devices and magnetic storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The schematic diagram of the structure of the edge nitrogen vacancy carbon nitride provided by the present invention, wherein: Figure 1 a is the complete structure of graphite-like carbon nitride. Figure 1 b is a schematic diagram of the structure producing edge nitrogen vacancies after annealing treatment.

[0029] Figure 2 This is a real optical photograph of the edge nitrogen vacancy carbon nitride provided by the present invention.

[0030] Figure 3 This is an atomic force microscope morphology image of the edge nitrogen vacancy carbon nitride provided by the present invention.

[0031] Figure 4 The transmission electron microscope image of the edge nitrogen vacancy carbon nitride provided by the present invention and the corresponding energy dispersion spectrum element distribution diagram, wherein: Figure 4 a is a transmission electron microscope image, Figure 4 b is the energy dispersion spectrum element distribution diagram of carbon element, Figure 4 c is the energy dispersion spectrum element distribution diagram of nitrogen element.

[0032] Figure 5 The X-ray diffraction spectrum of the edge nitrogen vacancy carbon nitride provided by the present invention.

[0033] Figure 6 The ultraviolet-visible absorption spectrum of the edge nitrogen vacancy carbon nitride provided by the present invention.

[0034] Figure 7 The Fourier transform infrared spectrum of the edge nitrogen vacancy carbon nitride provided by the present invention.

[0035] Figure 8 The temperature-magnetization intensity (MT) curve of the edge nitrogen vacancy carbon nitride provided by the present invention, wherein: Figure 8 a is the MT curve when the external magnetic field strength is H = 100Oe, Figure 8 b is the MT curve when the external magnetic field intensity is H=1000Oe.

[0036] Fig. 9 The magnetization curve of the edge nitrogen vacancy carbon nitride provided by the present invention at 2K.

[0037] Fig.10 The magnetization curve of the edge nitrogen vacancy carbon nitride provided by the present invention at 300K. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] like Figure 1 As shown, an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, the edge nitrogen vacancy carbon nitride is an amorphous nanosheet structure; the thickness of the amorphous nanosheet is 3-8nm, and the length or width is 1-15μm; the edge nitrogen vacancy carbon nitride retains a graphite-like phase structure while having a nitrogen vacancy at the edge of the carbon-nitrogen skeleton, that is, the amino group (-NH2) at the melamine unit (C6N7) is missing to form a nitrogen vacancy.

[0040] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, using urea as a raw material, sequentially calcining, grinding in argon and annealing to introduce nitrogen vacancies at the edges of the carbon-nitrogen skeleton of the graphite-like phase structure of the carbon nitride, and synthesizing the edge nitrogen vacancy carbon nitride, specifically comprising the following steps:

[0041] Step 1: placing urea in a muffle furnace, heating it to 550-650°C at 2.5-5°C / min, and then keeping it warm for 2-4h for calcining, and then naturally cooling it to room temperature to obtain g-C3N4 powder; the purity of the urea is greater than or equal to 99%; nitrogen vacancies are easily formed at this calcination temperature, and the carbon-nitrogen skeleton will be broken to form amorphous carbon nitride;

[0042] Step 2: The g-C3N4 powder obtained in step 1 is transferred to an argon-filled glove box, and is manually ground with a mortar for at least 30 minutes and then sieved to obtain a powder with a sieve mesh of 200-350 mesh; grinding under argon can avoid the introduction of oxygen elements, and at the same time, the g-C3N4 nanosheets are thinned by mechanical force, which is more conducive to the subsequent sufficient introduction of nitrogen vacancies;

[0043] Step 3: Spread the g-C3N4 powder in a quartz crucible and then place it in an argon-filled tube furnace for annealing to obtain an orange-red powder, such as Figure 2As shown; annealing conditions are: in an argon environment, heating to 680-800℃ at 25-35℃ / min and then keeping warm for 1-10min. Annealing at a higher temperature can promote the formation of more nitrogen vacancies and further form amorphous carbon nitride; the g-C3N4 powder used for annealing in the quartz crucible should not be greater than 10mg / mm 2 ;

[0044] Step 4: Wash the orange-red powder with dilute ammonia water, ethanol and deionized water with a molar concentration of 0.1-0.2 mol / L in sequence, and use each cleaning solution for at least three times. After washing, dry the powder to obtain edge nitrogen vacancy carbon nitride powder; the cleaning operation is ultrasonic oscillation and centrifugal removal, the ultrasonic oscillation time is ≤10min, the centrifugal speed is 4000-6000rpm, and the centrifugal time is ≥6min; the drying temperature is 60-80°C, and the drying time is at least 4h.

[0045] Example 1

[0046] The invention discloses an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, wherein the edge nitrogen vacancy carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a thickness of 3-4.1 nm and a length or width of 1-4.2 μm.

[0047] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, specifically comprising the following steps:

[0048] Step 1: Place 5 g of urea powder in a crucible and calcine in a muffle furnace at a heating rate of 2.5 °C / min to 550 °C, keep warm for 2 h, cool to room temperature after the insulation, and collect g-C3N4 powder in the crucible;

[0049] Step 2: The g-C3N4 powder was transferred to an argon-filled glove box, ground using an agate mortar for 30 min, and then sieved to obtain a powder with a sieve size of 200 mesh;

[0050] Step 3: Take 3 g of the powder obtained in step 2 and spread it in a quartz crucible with a length of 50 mm and a width of 10 mm, transfer it to an argon-filled tube furnace, heat it to 680°C at a rate of 25°C / min, keep it at that temperature for 1 min, and then immediately start to cool it naturally to room temperature to obtain an orange-red powder;

[0051] Step 4: Disperse the orange-red powder obtained in step 3 in dilute ammonia water with a molar concentration of 0.1 mol / L, ultrasonically oscillate for 10 minutes, then centrifuge at 6000 rpm for 10 minutes, remove the solution, retain the precipitate, repeat the dilute ammonia water washing three times, then add ethanol, repeat the ethanol washing three times, finally add deionized water, repeat the deionized water washing three times, and then place the final precipitate in an oven at 60°C and bake for 6 hours to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0052] Example 2

[0053] The invention discloses an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, wherein the edge nitrogen vacancy carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a thickness of 4.3-5.5 nm and a length or width of 3.1-6.8 μm.

[0054] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, specifically comprising the following steps:

[0055] Step 1: Place 5 g of urea powder in a crucible and calcine in a muffle furnace at a heating rate of 3 °C / min to 570 °C, keep the temperature for 2.5 h, cool to room temperature after the insulation, and collect g-C3N4 powder in the crucible;

[0056] Step 2: The g-C3N4 powder was transferred to an argon-filled glove box, ground using an agate mortar for 40 min, and then sieved to obtain a powder with a sieve size of 240 mesh;

[0057] Step 3: Take 3 g of the powder obtained in step 2 and spread it in a quartz crucible with a length of 50 mm and a width of 10 mm, transfer it to an argon-filled tube furnace, heat it to 700 ° C at 28 ° C / min, keep it warm for 3 minutes, and then immediately start to cool naturally to room temperature to obtain an orange-red powder;

[0058] Step 4: Disperse the orange-red powder obtained in step 3 in dilute ammonia water with a molar concentration of 0.15 mol / L, ultrasonically oscillate for 8 minutes, then centrifuge at 5000 rpm for 8 minutes, remove the solution, retain the precipitate, repeat the dilute ammonia water washing three times, then add ethanol, repeat the ethanol washing three times, and finally add deionized water, repeat the deionized water washing three times, and then place the final precipitate in an oven at 60°C and bake for 4 hours to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0059] Example 3

[0060] The invention discloses an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, wherein the edge nitrogen vacancy carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a thickness of 5.3-6.9 nm and a length or width of 7.2-10.6 μm.

[0061] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, specifically comprising the following steps:

[0062] Step 1: Place 5 g of urea powder in a crucible and calcine in a muffle furnace at a heating rate of 4 °C / min to 600 °C, keep warm for 3 h, cool to room temperature after the insulation, and collect g-C3N4 powder in the crucible;

[0063] Step 2: The g-C3N4 powder was transferred to an argon-filled glove box, ground using an agate mortar for 35 min, and then sieved to obtain a powder with a sieve mesh of 270 mesh;

[0064] Step 3: Take 3 g of the powder obtained in step 2 and spread it in a quartz crucible with a length of 50 mm and a width of 10 mm, transfer it to an argon-filled tube furnace, heat it to 730°C at a rate of 30°C / min, keep it warm for 5 min, and then immediately start natural cooling until the temperature drops to room temperature to obtain an orange-red powder;

[0065] Step 4: Disperse the orange-red powder obtained in step 3 in dilute ammonia water with a molar concentration of 0.2 mol / L, ultrasonically oscillate for 6 minutes, then centrifuge at 4000 rpm for 6 minutes, remove the solution, retain the precipitate, repeat the dilute ammonia water washing three times, then add ethanol, repeat the ethanol washing three times, finally add deionized water, repeat the deionized water washing three times, and then place the final precipitate in an oven at 70°C and bake for 4 hours to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0066] Example 4

[0067] The invention discloses an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, wherein the edge nitrogen vacancy carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a thickness of 6.3-7.8 nm and a length or width of 11.2-13.8 μm.

[0068] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, specifically comprising the following steps:

[0069] Step 1: Place 5 g of urea powder in a crucible and calcine in a muffle furnace at a heating rate of 4.5 °C / min to 630 °C, keep warm for 3.5 h, cool to room temperature after the insulation, and collect g-C3N4 powder in the crucible;

[0070] Step 2: The g-C3N4 powder was transferred to an argon-filled glove box, ground using an agate mortar for 60 min, and then sieved to obtain a powder with a sieve size of 350 mesh;

[0071] Step 3: Take 3 g of the powder obtained in step 2 and spread it in a quartz crucible with a length of 50 mm and a width of 10 mm, transfer it to an argon-filled tube furnace, heat it to 750 ° C at 33 ° C / min, keep it warm for 10 min, and then immediately start natural cooling until the temperature drops to room temperature to obtain an orange-red powder;

[0072] Step 4: Disperse the orange-red powder obtained in step 3 in dilute ammonia water with a molar concentration of 0.13 mol / L, ultrasonically oscillate for 10 minutes, then centrifuge at 4000 rpm for 12 minutes, remove the solution, retain the precipitate, repeat the dilute ammonia water washing three times, then add ethanol, repeat the ethanol washing three times, finally add deionized water, repeat the deionized water washing three times, and then place the final precipitate in an oven at 80°C and bake for 4 hours to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0073] Example 5

[0074] The invention discloses an edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, wherein the edge nitrogen vacancy carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a thickness of 4.3-8.2 nm and a length or width of 10.1-15 μm.

[0075] A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, specifically comprising the following steps:

[0076] Step 1: Place 5 g of urea powder in a crucible and calcine in a muffle furnace at a heating rate of 5 °C / min to 650 °C, keep warm for 4 hours, cool to room temperature after the insulation, and collect g-C3N4 powder in the crucible;

[0077] Step 2: The g-C3N4 powder was transferred to an argon-filled glove box, ground using an agate mortar for 45 min, and then sieved to obtain a powder with a sieve size of 300 mesh;

[0078] Step 3: Take 3 g of the powder obtained in step 2 and spread it in a quartz crucible with a length of 50 mm and a width of 10 mm, transfer it to an argon-filled tube furnace, heat it to 800 ° C at 35 ° C / min, keep it warm for 10 min, and then immediately start to cool naturally to room temperature to obtain an orange-red powder;

[0079] Step 4: Disperse the orange-red powder obtained in step 3 in dilute ammonia water with a molar concentration of 0.18 mol / L, ultrasonically oscillate for 10 minutes, then centrifuge at 5000 rpm for 10 minutes, remove the solution, retain the precipitate, repeat the dilute ammonia water washing three times, then add ethanol, repeat the ethanol washing three times, finally add deionized water, repeat the deionized water washing three times, and then place the final precipitate in an oven at 70°C for 5 hours to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

[0080] The edge nitrogen vacancy carbon nitride with room temperature ferromagnetism prepared in the above embodiments can be used in spin electronic devices, topological quantum devices and magnetic storage.

[0081] like Figure 1As shown, the edge nitrogen vacancy carbon nitride prepared by the present invention retains a graphite-like phase structure while the amino group (-NH2) at the melamine unit (C6N7) is missing to form a nitrogen vacancy.

[0082] like Figure 2 As shown, the optical photograph shows that the carbon nitride prepared by the present invention appears as orange-red powder.

[0083] like Figure 3 As shown, it can be seen from the atomic force microscope image that the carbon nitride prepared in the present invention has a two-dimensional layered structure of amorphous nanosheets, the thickness of the amorphous nanosheets is 3.4-8.2nm, and the length or width is 1-15μm.

[0084] like Figure 4 As shown, it can be seen from the transmission electron microscope image that the edge nitrogen vacancy carbon nitride prepared by the present invention shows a layered structure, carbon elements and nitrogen elements are evenly distributed in the sample, and the content of nitrogen element is relatively small, indicating that the carbon nitride prepared by the present invention is an amorphous carbon nitride nanosheet with nitrogen vacancies.

[0085] like Figure 5 As shown, the X-ray diffraction spectrum shows a broad amorphous diffraction peak at 21.5°, indicating that the carbon nitride prepared in the present invention is an amorphous material.

[0086] like Figure 6 As shown, the UV-visible absorption spectrum shows a broad and gentle absorption edge, indicating that the carbon nitride prepared by the present invention is amorphous.

[0087] like Figure 7 As shown, the carbon nitride prepared by the present invention contains chemical bonds in different states through Fourier transform infrared spectroscopy, namely 3300cm -1 、1600cm -1 With 1450cm -1 The absorption peaks at correspond to -NH2, -NH and C=N bonds respectively, among which the signal intensity of -NH2 bond is relatively low, indicating the existence of nitrogen vacancies at the melamine unit.

[0088] like Figure 8 As shown, the MT curves of the carbon nitride prepared by the present invention under zero field cooling (ZFC) and field cooling (FC) under external magnetic fields of 100Oe and 1000Oe still have ferromagnetic signals at a temperature of 400K, indicating that its Curie temperature is greater than 400K, indicating that the edge nitrogen vacancy carbon nitride prepared by the present invention is a room temperature ferromagnetic material.

[0089] like Fig. 9 and Fig.10As shown, the edge nitrogen vacancy carbon nitride prepared by the present invention has a saturation magnetization of 0.065emu / g at 2K, and a saturation magnetization of 0.045emu / g at 300K, indicating that the edge nitrogen vacancy carbon nitride prepared by the present invention has magnetic properties that can be actually used at room temperature.

[0090] It can be seen from the embodiments and the accompanying drawings that, compared with the prior art, the present invention can successfully prepare edge nitrogen vacancy carbon nitride with room temperature ferromagnetism without the need for additional introduction of doping elements, and its Curie temperature exceeds 400K, the saturation magnetization is not less than 0.065emu / g at a temperature of 2K, and the saturation magnetization is not less than 0.045emu / g at a temperature of 300K.

Claims

1. A method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism, characterized in that: Urea is used as a raw material, and calcination, grinding in argon and annealing are performed in sequence to introduce nitrogen vacancies at the edge of the carbon-nitrogen skeleton of the graphite-like phase structure of carbon nitride to synthesize edge nitrogen vacancy carbon nitride, which specifically includes the following steps: Step 1: calcine urea by heating it to 550-650°C at 2.5-5°C / min and then keeping it at that temperature for 2-4h, and then naturally cool it to room temperature to obtain g-C3N4 powder; Step 2: Grind and sieve the g-C3N4 powder obtained in step 1 in an argon-filled environment to obtain a powder with a sieve mesh number of 200-350 mesh; Step 3: The g-C3N4 powder obtained in step 2 is heated to 680-800°C at 25-35°C / min in an argon environment and then kept at this temperature for 1-10 minutes for annealing to obtain an orange-red powder; Step 4: Use a cleaning solvent to clean and dry the orange-red powder obtained in step 3 to obtain edge nitrogen vacancy carbon nitride powder with room temperature ferromagnetism.

2. The method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 1, characterized in that: The purity of urea in step 1 is greater than or equal to 99%.

3. The method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 1, characterized in that: The grinding time in step 2 is not less than 30 min.

4. The method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 1, characterized in that: The g-C3N4 powder used for annealing is not more than 10 mg / mm 2 .

5. The method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 1, characterized in that: The cleaning solvents in step 4 are diluted ammonia water, ethanol and deionized water with a molar concentration of 0.1-0.2 mol / L, and finally the cleaning is performed with deionized water. The cleaning times for each cleaning solvent are at least three times.

6. The method for preparing edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 1, characterized in that: The cleaning operation in step 4 is ultrasonic oscillation and centrifugal removal, the ultrasonic oscillation time is ≤10min, the centrifugal speed is 4000-6000rpm, and the centrifugal time is ≥6min; the drying temperature is 60-80°C, and the drying time is at least 4h.

7. An edge nitrogen vacancy carbon nitride with room temperature ferromagnetism obtained by the preparation method according to any one of claims 1 to 6.

8. The edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 7, characterized in that: The edge nitrogen vacancy carbon nitride is in the form of orange-red powder and has an amorphous nanosheet structure; the amorphous nanosheet has a thickness of 3-8 nm and a length or width of 1-15 μm.

9. The edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to claim 7, characterized in that: The edge nitrogen vacancy carbon nitride has nitrogen vacancies at the edges of the carbon-nitrogen skeleton while retaining a graphite-like phase structure.

10. Application of the edge nitrogen vacancy carbon nitride with room temperature ferromagnetism according to any one of claims 8 or 9 in spintronic devices, topological quantum devices or magnetic storage.

Citation Information

Patent Citations

  • Preparation method and application of sulfydryl-functionalized magnetic nitric carbonitride nano composite material

    CN115382505A